Genetic variability and agronomic performance studies in chilli (Capsicum annum L.) (SAARC Journal of Agriculture, 2017)
Eight diverse genotypes of chilli were evaluated an open field study to evaluate the genetic variability, heritability and genetic advance in randomized block design (RBD) with three replications during Kharif, 2015-16. Analysis of variance revealed significant differences among the genotypes for all the characters studied. The higher estimates of genotypic coefficient of variation (GCV) were observed for flowers per branch (21.59%), clusters per plant (19.26%), flower per branch (16.93%) and stem diameter (15.49%). While the higher estimates of phenotypic coefficient of variation (PCV) were found for flowers per branch (26.70%), fruits per branch (24.44%), clusters per plant (24.04%) and stem diameter (19.26%). The higher estimates of broad sense heritability along with genetic advance recorded for flowers per branch (65%), fruits per plant (64%), cluster per plant (64%), stem diameter (65%), plant weight (59%) and days to 50% flowering (50%) indicated the scope for improvement of these characters through selection.SAARC J. Agri., 14(2): 56-62 (2016)